Family counseling in the environment of Polish emigrants - Dubas, Elżbieta; Wąsiński, Arkadiusz; Słowik, Aneta; Agnieszka Gralak; Hrehorowicz, Uta; Demkowicz, Leszek (Biografie rodzinne i uczenie się: Tom 8, 2021)
The article presents the methods, places and ways of work of a family counselor in the environment of Polish emigrants. The author, using the interpretation of narrative interview, characterizes selected counseling practices initiated by a family counselor in the Polish community abroad in England and Germany. She recalls and describes some of the places of work of counsellors (e.g. counseling, social welfare and crisis intervention centers) in the pioneering communities of Polish emigrants (based on the Polish Peasant in Europe and America by William Thomas and Florian Znaniecki). She skillfully juxtaposes them with those present in contemporary narratives by putting stress on the sources and inspiration of becoming a counselor. The author shows that social counseling as well as crisis intervention is an important area of counseling, and that the roles of family counselor and social worker complement and interpenetrate each other.